2018
DOI: 10.1016/j.neo.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

SIRT2 Promotes the Migration and Invasion of Gastric Cancer through RAS/ERK/JNK/MMP-9 Pathway by Increasing PEPCK1-Related Metabolism

Abstract: Metastasis is the most important feature of gastric cancer (GC) and the most widely recognized reason for GC-related deaths. Unfortunately, the underlying mechanism behind this metastasis remains unknown. Mounting evidence suggests the dynamic regulatory role of sirtuin2 (SIRT2), a histone deacetylase (HDAC), in cell migration and invasion. The present study aims to evaluate the biological function of SIRT2 in GC and identify the target of SIRT2 as well as evaluate its therapeutic efficacy. We found that SIRT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 55 publications
7
100
0
Order By: Relevance
“…Apoptosis NSCLC [40] P53 CCA [41] MYC Metastasis HCC [42,43] AKT/GSK3β/β-catenin Axis GC [44] Tumorigenesis BC [45] Slug HCC [39] APC, CDC20 BC [39] APC, CDC20 SIRT3 Viability BLC [46] P53 PC [47] MYC; PI3K/AKT pathway CRC [48] AKT/PTEN NSCLC [49] Bax/Bcl-2, P53 HCC [50] PI3K/AKT pathway PDC [51] Apoptosis NSCLC [49] Bax/Bcl-2, P53 OSCC [52] RIP Leukemia [53] AKT, Bax/Bcl-2 Metastasis CRC [48] AKT/PTEN HCC [50] PI3K/AKT pathway PDC [51] PC [54] FOXO3A, Wnt/β-catenin pathway OC [55] Twist [57] ERK/Drp1 Axis ESCC [58] GDH CRC [59] GC [60] Apoptosis Metastasis NSCLC [57] ERK/Drp1 Axis ESCC [58] GDH CRC [59] E-cadherin GC [60] E-cadherin [72] COX-2, AKT, AMPK CRC [73] PTEN/AKT signaling ACC [74] NF-κB signaling GBM [75] JAK2/STAT3 pathway Apoptosis CRC [73] PTEN/AKT signaling HCC [70] Bax GBM [75] AK2/STAT3 pathway FSA [76] NF-κB signaling HCC [77,78] ERK1/2 pathway CC [76] NF-κB signaling Metastasis HCC [71,79] PKM2 CRC…”
Section: Sirtuins and Viability In Cancersmentioning
confidence: 99%
“…Apoptosis NSCLC [40] P53 CCA [41] MYC Metastasis HCC [42,43] AKT/GSK3β/β-catenin Axis GC [44] Tumorigenesis BC [45] Slug HCC [39] APC, CDC20 BC [39] APC, CDC20 SIRT3 Viability BLC [46] P53 PC [47] MYC; PI3K/AKT pathway CRC [48] AKT/PTEN NSCLC [49] Bax/Bcl-2, P53 HCC [50] PI3K/AKT pathway PDC [51] Apoptosis NSCLC [49] Bax/Bcl-2, P53 OSCC [52] RIP Leukemia [53] AKT, Bax/Bcl-2 Metastasis CRC [48] AKT/PTEN HCC [50] PI3K/AKT pathway PDC [51] PC [54] FOXO3A, Wnt/β-catenin pathway OC [55] Twist [57] ERK/Drp1 Axis ESCC [58] GDH CRC [59] GC [60] Apoptosis Metastasis NSCLC [57] ERK/Drp1 Axis ESCC [58] GDH CRC [59] E-cadherin GC [60] E-cadherin [72] COX-2, AKT, AMPK CRC [73] PTEN/AKT signaling ACC [74] NF-κB signaling GBM [75] JAK2/STAT3 pathway Apoptosis CRC [73] PTEN/AKT signaling HCC [70] Bax GBM [75] AK2/STAT3 pathway FSA [76] NF-κB signaling HCC [77,78] ERK1/2 pathway CC [76] NF-κB signaling Metastasis HCC [71,79] PKM2 CRC…”
Section: Sirtuins and Viability In Cancersmentioning
confidence: 99%
“…Recently, SIRT2 was found to be associated with mitotic cell cycle control [11][12][13], in which SIRT2 likely promoted tumorigenesis [14][15][16][17]. Upregulation of SIRT2 has been detected in a number of tumors [16][17][18][19][20][21][22]. However, it is not known whether SIRT2 is a CSC marker in cancers, including RCC.…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, HDAC2 could bind to different loci on chromosome 11 and can modulate MMP27 bidirectionally. Previous studies suggested that the HDAC family could regulate multiple MMPs, including MMP1, MMP2, MMP3, MMP7, MMP9, MMP10, MMP13, MMP14, and MMP28, 23‐28 and that MMP10 could be regulated by HDAC3 and HDAC7 28,29 . For the first time, we found that HDAC2 could potentially modulate the MMP10, MMP16, MMP21, MMP25‐AS1, MMP27, and CD16 genes in neutrophils of AIS patients.…”
Section: Discussionmentioning
confidence: 55%